2021
DOI: 10.1158/2159-8290.cd-20-1598
|View full text |Cite|
|
Sign up to set email alerts
|

Activity and Safety of Mobocertinib (TAK-788) in Previously Treated Non–Small Cell Lung Cancer with EGFR Exon 20 Insertion Mutations from a Phase I/II Trial

Abstract: Mobocertinib, an oral epidermal growth factor receptor (EGFR) inhibitor targeting EGFR gene mutations, including exon 20 insertions (EGFRex20ins), in non–small cell lung cancer, was evaluated in a phase I/II dose-escalation/expansion trial (ClinicalTrials.gov NCT02716116). Dose escalation identified 160 mg/d as the recommended phase 2 dose and maximum tolerated dose. Among 136 patients treated with 160 mg/d, the most common any-grade treatment-related adverse events (TRAE; >25%) were diarrhea (83%), nau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
160
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(181 citation statements)
references
References 48 publications
3
160
0
1
Order By: Relevance
“…Mobocertinib at 160 mg daily was chosen as the maximum tolerated dose and the recommended phase 2 dose (RP2D). 5 Pharmacokinetic data showed mobocertinib had a median time to maximum plasma concentrations (T max ) of 4 hours and a geometric mean effective half-life of 11-17 hours across the 20 to 160 mg daily dosing based on accumulation. Following administration of mobocertinib from 5 to 180 mg orally daily, the area under the concentration-time curve from time 0 to 24 hours (AUC 0-24 ) increased in a dose-dependent manner.…”
Section: Clinical Data Phase 1 Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobocertinib at 160 mg daily was chosen as the maximum tolerated dose and the recommended phase 2 dose (RP2D). 5 Pharmacokinetic data showed mobocertinib had a median time to maximum plasma concentrations (T max ) of 4 hours and a geometric mean effective half-life of 11-17 hours across the 20 to 160 mg daily dosing based on accumulation. Following administration of mobocertinib from 5 to 180 mg orally daily, the area under the concentration-time curve from time 0 to 24 hours (AUC 0-24 ) increased in a dose-dependent manner.…”
Section: Clinical Data Phase 1 Resultsmentioning
confidence: 99%
“…Dose interruption, dose reduction, and dose discontinuation was seen in 74 (54%), 23 (17%), and 22 (16%) patients, respectively. 5 The efficacy of mobocertinib was assessed among 70 previously treated NSCLC patients harboring EGFR ex20ins mutations from both the phase 1 and the phase 2 portions, including 12 patients in 5-40mg daily cohorts, nine in 80 mg total daily (80 mg daily and 40 mg twice daily), 21 in 120 mg daily, and 28 in 160 mg daily. 5 More specifically, these 28 patients treated with mobocertinib at 160 mg daily had not received (N = 22) or responded (N = 6) to a previous EGFR TKI.…”
Section: Phase 2 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osimertinib has also demonstrated activity against uncommon activating EGFR mutations in a single-arm phase II study [25]. Treatment options for exon 20 mutations remain an unmet need, but several agents are in clinical development such as poziotinib and mobocertinib which has shown promise in phase II trials [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a phase III study of mobocertinib (TAK-788), a novel, irreversible, small-molecule EGFR inhibitor speci cally designed to target exon 20 insertion mutants, has been conducted in patients with advanced NSCLC harboring these mutations 33 . Preclinical data and phase I/II studies have reported that mobocertinib demonstrates antitumor activity with manageable toxicity in patients with advanced EGFR exon 20 insertion mutations 33,34 . Furthermore, the phase 1 CHRYSALIS trial (NCT02609776) showed that amivantamab, a bispeci c antibody directed against EGF and MET receptors, induces an objective response in 40% of patients with previously treated NSCLC harboring EGFR exon 20 insertion mutations, with 47% maintaining their response for at least 6 months and 47% remaining on therapy after a median follow-up of over 9 months 35 .…”
Section: Discussionmentioning
confidence: 99%